IMPLEMENTASI POLIS ASURANSI JIWA SEBAGAI OBJEK JAMINAN TAMBAHAN DALAM MITIGASI RISIKO PEMBIYAAN PADA BANK (Studi di PT. Bank Sumatera Utara Syariah Cabang Medan) - Pratiwi Nurhayati; Adlin Budhiawan (UNES Law Review, 2023)
This journal discusses the role of life insurance policies as additional collateral in bank financing to minimize the risk of default by customers. It is also explained that life insurance policies are considered intangible movable property with an economic value that can be monetized. Although not the primary collateral, life insurance policies can be used as supplementary collateral to minimize financing risks. Banks can collaborate with insurance companies through the concept of Bancassurance to facilitate the process of opening and claiming life insurance policies. The cash value of life insurance policies can be taken into consideration as collateral for credit, provided that the collateralization is done formally, and the collateral can be sold or cashed out to settle the debtor's obligations. This research employs a juridical-empirical legal research method with a qualitative approach. The research results show that life insurance policies play a significant role in minimizing financing risks and protecting banks from default risks by debtors. The purchase or opening of life insurance as a requirement for financing is not explicitly regulated by the Financial Services Authority Regulation No. 42 of 2017 regulations but is an internal bank policy.